Local deformation for soft tissue simulation. Issue 5 (2nd September 2016) - Omar, Nadzeri; Zhong, Yongmin; Smith, Julian; Gu, Chengfan
ABSTRACT: This paper presents a new methodology to localize the deformation range to improve the computational efficiency for soft tissue simulation. This methodology identifies the local deformation range from the stress distribution in soft tissues due to an external force. A stress estimation method is used based on elastic theory to estimate the stress in soft tissues according to a depth from the contact surface. The proposed methodology can be used with both mass-spring and finite element modeling approaches for soft tissue deformation. Experimental results show that the proposed methodology can improve the computational efficiency while maintaining the modeling realism.